2018
DOI: 10.3389/fpsyg.2018.00246
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Divide: The Role of Motivation and Self-Regulation in Explaining the Judgment-Action Gap Related to Academic Dishonesty

Abstract: There is often a divide between moral judgment and moral action; between what we believe we ought to do (or not do) and what we do. Knowledge of this divide is not new, and numerous theories have attempted to offer more robust accounts of ethical decision-making and moral functioning. Knowledge of widespread academic dishonesty among students is also not new, and several studies have revealed that many students report cheating despite believing it is wrong. The present study, involving cross-sectional survey d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 66 publications
0
26
0
3
Order By: Relevance
“…Along with grades and personality, morals and norms also appear in the literature on academic misconduct (Park, 2003; Stephens, 2018) and have strong ties with each other (Posner and Rasmusen, 1999). Franklyn-Stokes and Newstead (1995) noted that students predominantly did not engage in assignment purchasing due to the perception of the behaviour as immoral and dishonest.…”
Section: Introductionmentioning
confidence: 99%
“…Along with grades and personality, morals and norms also appear in the literature on academic misconduct (Park, 2003; Stephens, 2018) and have strong ties with each other (Posner and Rasmusen, 1999). Franklyn-Stokes and Newstead (1995) noted that students predominantly did not engage in assignment purchasing due to the perception of the behaviour as immoral and dishonest.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, for these three factors, a significantly greater proportion of participants used the first two points of the five-point scale (i.e., Never and Once or twice this year ) relative to latter end of the scales (i.e., About weekly and Almost daily ). This was not unexpected as significant positive skews are typical on the AMIS (e.g., Stephens, 2018 ) as well as other measures of academic dishonesty (e.g., Anderman et al, 1998 ).…”
Section: Resultsmentioning
confidence: 72%
“…Relations between judgments and actions have received a great deal of theoretical and empirical attention (Blasi, 1980;Thoma, 1994;Stephens, 2018;Turiel, 2003;Waltzer et al, 2019). Previous research has found that people's judgments and values largely guide their behaviors (Ajzen, 1985(Ajzen, , 1988(Ajzen, , 1991Ajzen & Fishbein, 2005;Knafo et al, 2011;Schwartz, 2012).…”
Section: Future Directions For Researchmentioning
confidence: 99%